The Effect of Cognitive Structure and Social Attitudes on System Justification Motivation - Şeker, B. Dilara; Akman Direkçi, Emine (Border Crossing, 2022)
System legitimation theory uses supportive ideologies and stereotypes to sustain existing systems in society. The main purpose of this study is to examine the role of cognitive structure, which is effective in legitimizing the current system in which individuals live, with the need for cognitive closure, and the role of social attitudes with right-wing authoritarianism and social dominance orientation. A total of 394 people, 203 women and 191 men, between the ages of 23-55, living in Manisa and its surroundings, voluntarily participated in the study. The relationship of the participants’ tendencies to legitimize the system with various demographic variables (age, gender, marital status, longest place of residence, religious and political orientation), cognitive closure need, right-wing authoritarianism, and social dominance orientation variables were analyzed in three steps by hierarchical multiple regression analysis. It was observed that the gender, marital status, religious and political tendencies of the participants significantly predicted their tendency to legitimize the system. It has been observed that the need for cognitive closure and the right wing authoritarianism and social dominance orientation, which form the dual process model, positively predict the tendency to legitimize the system.